THE INFLUENCE OF GREEN PERCEIVED QUALITY AND GREEN PERCEIVED RISK ON GREEN SATISFACTION AND GREEN TRUST OF SHARP AIR-CONDITIONING IN SURABAYA - Patricia Kelly Yuwono (CALYPTRA, 2017)
Abstract – This research is conducted to find out the influence of green perceived quality and green perceived risk on green satisfaction and green trust of consumers of Sharp Air-Conditioning in Surabaya. The model in this study used five hypotheses. This research is causal research with quantitative method. This study used purposive sampling approach, which the sample consists of respondents who have bought and experience Sharp Air-Conditioning in Surabaya within one year. There are 190 respondents in this study. The analysis in this study used a model of SEM (Structural Equation Modeling), and processed using SPSS 20.0 for WINDOWS and LISREL 8.80 for Measurement and Structural Model. The result shows that green perceived quality and green perceived risk has influence on consumer green satisfaction of Sharp AirConditioning in Surabaya. Moreover, green perceived quality, green perceived risk, and green satisfaction has influence on consumer green trust of Sharp AirConditioning in Surabaya. Keywords: Green Perceived Quality, Green Perceived Risk, Green Satisfaction, Green Trust